Cholecystokinin neurons in the spinal trigeminal nucleus interpolaris regulate mechanically evoked predatory hunting in male mice - Dandan Geng; Yaning Li; Bo Yang; Li Zhang; Huating Gu; Tianyun Zhang; Zijie Zhao; Hui Liu; Qingzhuo Cui; Rong Zheng; Peng Cao; Fan Zhang (Nature Communications)
Abstract Predatory hunting plays a critical role in animal survival. Motion-related vibrissal somatosensory signaling is essential for prey detection and hunting in mice. However, little is known about the neural circuits that convert vibrissal somatosensory cues to trigger predatory hunting. Here, we report that mechanical force onto the vibrissal area of the male mice is a key stimulus for predatory hunting. Mechanically evoked predatory hunting was abrogated by the chemogenetic inactivation of cholecystokinin-positive (Cck+) neurons in the spinal trigeminal nucleus interpolaris (Sp5I). The Cck+ Sp5I neurons responded to the intensity of mechanical stimulus and sent neural signals to the superior colliculus that were relevant to stereotypical predatory hunting motor actions. Synaptic inactivation of the projections from Cck+ Sp5I neurons to the superior colliculus impaired mechanically evoked predatory attacks. Together, these data reveal a spinal trigeminal nucleus neural circuit that is specifically engaged in translating vibrissal somatosensory cues to provoke predatory hunting.